AbobotulinumtoxinA and rehabilitation vs rehabilitation alone in post-stroke spasticity: A cost-utility analysis - Carlo Lazzaro; Alessio Baricich; Alessandro Picelli; Patrizia Maria Caglioni; Marco Ratti; Andrea Santamato (Medical Journals Sweden, 2020)
Objective: To investigate costs and quality-adjusted life years of rehabilitation combined with abobotulinumtoxinA (aboBoNT-A) (rehab/aboBoNT-A) vs rehabilitation alone (rehab) in post-stroke spasticity in Italy. Design: Based on both Italian National Health Service and societal perspectives, a 2-year cost-utility analysis model was performed. Subject/patients: The cost-utility analysis model considered hypothetical patients. Methods: The cost-utility analysis model was populated with data concerning demographics, disease severity, healthcare and non-healthcare resource consumption. Data were collected via a questionnaire administered to 3 highly experienced Italian physiatrists (864 out of 930 post-stroke spasticity patients on rehab/aboBoNT-A in total). Costs are expressed in Euro (€) based on the year 2018. Results: The cost to society (rounded to the nearest whole €) was €22,959 (rehab/aboBoNT-A) vs €11,866 (rehab). Italian National Health Service-funded cost was €7,593 (rehab/aboBoNT-A) vs €1,793 (rehab). Over a period of 2 years rehab/aboBoNT-A outperforms rehab in terms of quality-adjusted life years gained (1.620 vs 1.150). The incremental cost-utility ratio was €12,341 (Italian National Health Service viewpoint) and €23,601 (societal viewpoint). Sensitivity analyses confirmed the robustness of the baseline results. Conclusion: Despite some limitations, the higher number of quality-adjusted life years gained vs rehab and the high probability of reaching a cost-utility ratio lower than the Italian informal acceptability range (€25,000-40,000) make rehab/aboBoNT-A a cost-effective healthcare programme for treating patients with post-stroke spasticity in Italy.